Hubungan Pengetahuan, Konsumsi Makanan Kariogenik dan Kebiasaan Menggosok Gigi dengan Kejadian Karies Gigi pada Remaja di One Icon Dental Clinic Gresik - Devia Dwi Ramadanty; Ervi Suminar; Diah Fauzia Zuhroh (Pusat riset dan Inovasi Nasional, 2025)
Dental caries is damage to hard tooth tissue caused by bacterial metabolism in plaque that results in demineralization. This study aims to analyze the relationship between knowledge, consumption of cariogenic foods and tooth brushing habits with the incidence of dental caries in adolescents at One Icon Dental Clinic Gresik. Using an analytical survey method with a cross-sectional design, this study involved 118 adolescent respondents selected through accidental sampling. Data were collected using a questionnaire and analyzed using the chi square and Spearman Rank tests. The results showed a significant relationship between knowledge (p = 0.000, r = 0.621), consumption of cariogenic foods (p = 0.000, r = 0.792), and tooth brushing habits (p = 0.043) with the incidence of dental caries. It can be concluded that there is a relationship between the three variables and the incidence of dental caries in adolescents at One Icon Dental Clinic Gresik